Fear of Missing Out Among High School Students in Bandung - Yosep, Iyus; Mardhiyah, Ai; Fitria, Nita; Lukman, Mamat; Hikmat, Rohman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Fear of Missing Out (FoMO) has become an increasingly common phenomenon among adolescents, especially with the increasing use of social media. FoMO can have a negative impact on students' mental well-being, which can result in anxiety, stress, and life dissatisfaction. This study is important to understand the level of FoMO among high school students, as well as the factors that influence it. With the increasing exposure of adolescents to social media, understanding FoMO becomes very relevant to developing effective interventions. This study aims to provide an overview of the level of FoMO among high school students in Bandung. Thus, the results of the study are expected to be the basis for efforts to improve mental health in educational environments. This study aims to describe the level of FoMO in high school students in Bandung and identify the factors that influence it. The design of this study was descriptive with a total sampling technique, involving 100 high schools students in Bandung. Data were collected through a questionnaire using the Online Fear of Missing Out (ON-FoMO) Scale, which consists of 20 questions adapted into Indonesian. Data analysis was carried out using frequency distribution to describe the characteristics of respondents and the level of FoMO. The results showed that the majority of respondents had moderate levels of FoMO, with 30% of respondents experiencing high FoMO. Factors that influence the level of Fear of Missing Out (FoMO) include age, gender, and class, where female students and adolescents tend to experience higher FoMO due to social pressure and intense social media interactions. The impacts of high FoMO can include increased anxiety, stress, and life dissatisfaction, which can affect students' overall psychological well-being. This study provides insight into the level of FoMO among high school students in Bandung, emphasizing the need for interventions to manage the negative impact of social media on students' mental well-being.